STUDI FENOMENOLOGI PENGALAMAN DAN PENGOBATAN PASIEN KANKER SERVIKS - Sri Ratna; Asriwati Asriwati; Ivansri Marsaulina (Jurnal Keperawatan Priority, 2022)
Cancer affects all aspects of a patient's life physically, psychologically, and spiritually. This study aimed to analyze the experience of cervical cancer patients. This study used a qualitative research method with a descriptive phenomenological approach. The participants consisted of key informants, namely 1 doctor, 5 main informants, and 5 cancer survivors The data in this study include primary data, secondary data, and tertiary data. Data were collected by three methods, namely, observation, interviews, and documentation. Data analysis was carried out by interactive analysis. The results of the study revealed 5 themes, namely: 1) family support, 2) sexual activity, 3) personal hygiene, 4) social relationships, and 5) the treatment process. Family support is the main factor that makes patients excited about undergoing treatment, while undergoing cancer services, patients continue to have sexual relations with their husbands, but the frequency is reduced from before undergoing treatment, in general, cervical cancer sufferers do not lack hygiene, cancer sufferers Cervical sufferers experience low self-esteem related to the disease they are suffering from, when they were first diagnosed with cervical cancer, the patient did not accept it, felt hopeless, and feared death. Based on the foregoing, it was concluded that when the informant had cancer, the patient really needed family support, besides that they continued to carry out sexual activities, paid less attention to personal hygiene, did not socialize, and tried to routinely take treatment, so it was suggested that the family be more supportive of the patient is undergoing treatment.